Indivíduos sem religião: desencantamento metafísico do mundo - Silva, Antonio Leandro da (2012)
Our goal is aimed at the understanding of some individuals existence, whose humane attitude is deprived of a religious mentality, that is, an orientation based on theological ends. The empirical study has been conducted with students who were preparing for college entrance exams and university students at Educafro SP Institution Education and Citizenship for Afro-Descendants and the Needy. Overall, the data through graphics were distributed into six variables: genre, age, schooling, skin color, social background, religion. Afterwards, we traced the survey individuals specifically: those without religion. For this second phase we used the qualitative survey which provided us with empirical elements to the construction of ideal types of individuals who claim not to have a religion. This way we realize that when we talk about those without religion we cannot fail to consider a path which forks into two and that interrelate, demanding from the researcher caution in the statistics analysis. But it weren t the quantitative data which pointed out to such forking, but the surveys in depth. Through them we could see that the first forking indicates a displacement of the existential disposition of an individual type who denies being part of a religion as a system of dogmas, symbols and moral and cultic practices, but they still consider themselves able to musical disposition for religiosity. On the other hand, the second forking and this one is a novelty which we thing it as a thesis that is not found in survey nowadays it relates directly to a kind of individual who doesn t manifest elements neither of religiosity nor religion itself. Those individuals we name them individuals without potential aptitude ( charisma , special gifts ) for religiosity or for religion. They do not live their lives based on religious values, that is, by a religious moral which interferes in their values and inner interests of religion practices or religion itself, other interests get more relevance, leading to their assertion of existence. This attitude was possible only due to the happening of, God s death which resulted in the disenchantment of the metaphysical world. This implies the religion departure of the existence of some individuals, being replaced by an ethics based on the amor fati . This perspective suggests not only over coming the religious metaphysical world, but also and introduction of a new dynamic interpretation on the individual s existence. This ethics presupposes a conscience deprived of any religious contents by which to guide one self. It implies in saying: the individual freed himself from that conscience foundation the sense between the guilt and duty notions and their religious presupposing: intertwining between evil conscience with the notion of God. God s death favored, therefore, considerable decline on the guilty conscience. Starting off from theoretical presupposing of weberian Comprehensible Sociology and nietzschian Existential Philosophy, as well as our interviewee s narratives, we have built a typology and a conceptualizing of those without religion: individuals who do not have religious aptitude, do not possess inner sensitivity in the sense of special disposition, inborn, from religiosity, so they can have the habit for religion